Proceso atención de enfermería en adolescente con úlcera péptica. - Salvatierra García, Geomayra Elizabeth (2021)
Peptic ulcer or peptic ulcer disease, is a disease that causes lesions in the gastrointestinal tract, it is located in the stomach altering the defense mechanism that protects the stomach from gastric juices, between 10-20% of cases it is caused by a one of the main causes is infection by a bacterial agent called Helicobacter pylori. Most people do not realize this type of infection, because the symptoms can be confused with other pathologies such as the presence of abdominal pai, weight loss, dehydration, vomiting, among others. This clinical case study aims to develop the nursing process in a 12-year-old adolescent patient who was diagnosed with peptic ulcer. Despite the fact that from the emergency area he was treated for different symptoms, once he was hospitalized, it was possible to corroborate his true etiology, through the pertinent evaluations of the patient as the reason for consultation, a meticulous cephalocaudal evaluation and their respective examinations, which emphasized the causes. And factors that led him to have a peptic ulcer, identifying the causative agent of this pathology, the gram-negative bacterium Helicobacter pylori; and then proceed to the elaboration of the nursing care process according to the dysfunctional patterns affected in the patient’s health, concluding with the adequate follow-up of the clinical picture regarding the pertinent treatment, in order to meet the goals and objectives proposed before this case study.